2022
DOI: 10.1155/2022/5478088
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Information and Communication Technology (ICT)-Based and Conventional Methods of Instruction on Learners’ Academic Enthusiasm for L2 Learning

Abstract: The present study aimed to compare the effects of information and communication technology (ICT)-based and conventional methods of instruction on ninth-grade students’ academic enthusiasm for L2 learning (English). The statistical population included all ninth-grade students from lower secondary schools for girls located in the city of Tehran, Iran, in 2019–2020. For this purpose, applied research with a quasiexperimental design was employed to meet the study objectives. To select the statistical sample, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…The teachers also showed that teaching through the experience of learning loss contributes to increasing their motivation towards developing their teaching skills and relying on teaching methods and methods that motivate students and increase their motivation. This result is consistent with what was indicated by many previous studies (Fannakhosrow, et al, 2022;Donnelly & Patrinos, 2021;Tashtoush, et al, 2022 b;Wahyudi, 2021;Rasheed & Tashtoush, 2021, Tashtoush, et al, 2020.…”
Section: Discussing the Results Of The Fourth Question: What Are The ...supporting
confidence: 93%
See 1 more Smart Citation
“…The teachers also showed that teaching through the experience of learning loss contributes to increasing their motivation towards developing their teaching skills and relying on teaching methods and methods that motivate students and increase their motivation. This result is consistent with what was indicated by many previous studies (Fannakhosrow, et al, 2022;Donnelly & Patrinos, 2021;Tashtoush, et al, 2022 b;Wahyudi, 2021;Rasheed & Tashtoush, 2021, Tashtoush, et al, 2020.…”
Section: Discussing the Results Of The Fourth Question: What Are The ...supporting
confidence: 93%
“…Moreover, the subject of learning loss was presented through some strategies. Teaching methods are compatible with students' needs, as indicated by previous studies (Tashtoush, et al, 2022 a;Fannakhosrowet, et al, 2022;Schult, et al, 2021;Tashtoush, et al, 2020 a). The prolonged interruption in the educational process during the Corona pandemic resulted in educational, psychological, and moral dangers, and social roles played a negative role in widening the educational gap, as students lost their right to education, classroom interaction, learning from their peers, unloading their energies, and, most importantly, preventing them from accessing the hidden curriculum that would otherwise be available to them.…”
mentioning
confidence: 72%
“…The results showed that 58.2% of the teachers reached the level of their mental habits of the third level (practice habits of mind) and the fourth level (practice habits of mind significantly), which constitutes more than half of the teachers. This is consistent with many previous studies that indicated the effectiveness of using training programs in developing the levels of habits of mind (Agyei & Voogt, 2014;Al-Jizani & Warad, 2012;Fannakhosrow et al, 2022;Makamure & Jita, 2019;Tashtoush et al, 2022;Tinh et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…By reviewing the theoretical and research literature, as well as looking at some scales of habits of mind in math (Assadi & Hibi, 2020;Berisha & Vula, 2021;Fannakhosrow et al, 2022;Tinh et al, 2021;), a standing scale was prepared at the form of a questionnaire according to the 5-choice Likert scale, that consisted of 30 items that included three sub-scales (thinking flexibly, metacognition, and questioning & posing problems), with a maximum score of 150 and a minimum score of 30.…”
Section: The Habits Of Mind Scalementioning
confidence: 99%
“…The findings of this study show that FCI effectively improves students' AP. This finding is consistent with the findings of (Bouwmeester et al, 2019;Burrows, 2010;Chang et al, 2022;Chen et al, 2018;Douglas, 2022;Fannakhosrow et al, 2022;McLean et al, 2016;Polat & Yilmaz, 2022;Wang & Holcombe, 2010;Wang et al, 2011) and inconsistent with Laura-De La Cruz et al ( 2022), Li et al (2022), Pratiwi et al (2022) findings. In explaining this finding, AP can be considered an activity that motivates active learning.…”
Section: Discussionsupporting
confidence: 82%